* WikiGenDex: A new gender identification algorithm based on open sources - González-Salmón, Elvira; Robinson-García, Nicolás (Infonomy, 2024)
Given the limitations found in other name-based gender assignment algorithms, we present a new algorithm based on open sources: WikiGenDex. This algorithm is based on information from Wikidata and the World Gender Name Dictionary (belonging to the World Intellectual Property Organization). Throughout the note we explain its mechanism, validate its operation, offer an example and a tutorial to use it with any name database.